Advancements in electrochemical energy storage: A review of biomass-derived separator, binder and electrolyte for electric vehicle battery - Damilare Samuel Oyebamiji; Davannendran Chandran; Revathi Raviadaran (Results in Engineering)
This paper aims to critically appraise the potential of biomass-derived separator, binder and electrolyte for electric vehicle (EV) battery application. Existing studies highlighted that conversion techniques used to derive these battery components from biomass via pretreatment, polymerization, neutralization, lyophilisation and carbonization influence key battery properties such as ionic conductivity, thermal stability and the potential for short-circuit. Use of biomass-derived separator in EV battery can enhance safety and extend life cycle by minimizing risks of short-circuit due to its thermal stability. Also, its mechanical strength to withstand vibration and internal stress makes it a viable alternative to conventional glass fibre and polypropylene. Adoption of biomass-derived binder for EV battery electrodes can enhance reversibility and durability due to its structural stability, high adhesion and wettability. Also, its ability to reduce mass loss and prevent degradation with improved thermal stability can improve safety, driving range and durability of EV battery. Self-healing compatibility and mechanical flexibility of biomass-derived electrolyte can enhance battery safety, durability and stability by improving electrochemical performance for EV application which can improve driving range. Integration of components derived from biomass is necessary to enhance driving range, durability and safety of EV. However, ensuring consistent material properties and battery performance at high temperatures and extended cycles, along with addressing challenges in energy density, electrochemical stability, large-scale production and conversion efficiency is crucial before displacing conventional materials. Future research should leverage on the use of machine learning to predict material properties and develop molecular and electrochemical models to minimize experimental work.